2022
DOI: 10.1002/lio2.853
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation and vocal fold biomechanics in a recurrent laryngeal nerve injury model

Abstract: Objectives/hypothesis Composite vocal fold (VF) biomechanical data are lacking for augmentation after recurrent laryngeal nerve (RLN) injury. We hypothesize resulting atrophy decreases VF stiffness and augmentation restores native VF biomechanics. Methods Sixteen Yorkshire Crossbreed swine underwent left RLN transection and were observed or underwent carboxymethylcellulose (CMC) or calcium hydroxyapatite (CaHa) augmentation at 2 weeks. Biomechanical measurements (structural stiffness, displacement, and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Early injection laryngoplasty with long-lasting fillers [ 47 ] has recently been recommended by scholars for this group of patients. While proper human studies are difficult to design, a recent animal study [ 48 ] performed using recurrent laryngeal nerve resection swine also demonstrated that early injection with calcium hydroxyapatite may improve biomechanical properties and slow thyroarytenoid muscle atrophy compared to the uninjured vocal fold, which is comparable to our protocol and results.…”
Section: Discussionsupporting
confidence: 75%
“…Early injection laryngoplasty with long-lasting fillers [ 47 ] has recently been recommended by scholars for this group of patients. While proper human studies are difficult to design, a recent animal study [ 48 ] performed using recurrent laryngeal nerve resection swine also demonstrated that early injection with calcium hydroxyapatite may improve biomechanical properties and slow thyroarytenoid muscle atrophy compared to the uninjured vocal fold, which is comparable to our protocol and results.…”
Section: Discussionsupporting
confidence: 75%
“…Euthanasia was performed after general anesthesia induction with intravenous pentobarbital (100 mg/kg) and confirmed via vital sign monitoring according to institutional protocol. The larynx was extracted immediately after euthanasia and sectioned in the sagittal plane, with care taken to preserve the anterior commissure 24–26 . Specimens were then frozen at −80°C until biomechanical and subsequent histologic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Each specimen was positioned beneath a camera to align a template with predetermined indentation points along the entire glottis and subglottis (Figure 2A). Normal indentation was conducted using a Biomomentum Mach‐1 v500css (Laval, Quebec, Canada) with a 1.5 N uniaxial load call as previously established 26,27 . For our evaluation, a 2 mm spherical indenter tip with a velocity of 1.2 mm/s and indentation depth of 0.3 mm was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work evaluating the effect of injection augmentation on vocal fold stiffness in an RLN injury model demonstrated biomechanical changes in the injected fold and compensatory changes in the healthy contralateral side. 14 While the thyroarytenoid area was significantly decreased after RLN transection and unaffected by injection augmentation, vocal fold stiffness on the injected side was closer to native tissue properties than the untreated denervated vocal fold. Perhaps more interesting, however, was that healthy vocal folds contralateral to an injected vocal fold also showed increased stiffness, suggestive of compensatory changes separate from the biomechanical properties of the injectate itself.…”
Section: Introductionmentioning
confidence: 91%